Highly Efficient Ambient Temperature CO2 Photomethanation Catalyzed by Nanostructured RuO2 on Silicon Photonic Crystal Support. Issue 9 (11th January 2018) - Jelle, Abdinoor A.; Ghuman, Kulbir K.; O'Brien, Paul G.; Hmadeh, Mohamad; Sandhel, Amit; Perovic, Doug D.; Singh, Chandra Veer; Mims, Charles A.; Ozin, Geoffrey A.
Abstract: Sunlight‐driven catalytic hydrogenation of CO2 is an important reaction that generates useful chemicals and fuels and if operated at industrial scales can decrease greenhouse gas CO2 emissions into the atmosphere. In this work, the photomethanation of CO2 over highly dispersed nanostructured RuO2 catalysts on 3D silicon photonic crystal supports, achieving impressive conversion rates as high as 4.4 mmol gcat −1 h −1 at ambient temperatures under high‐intensity solar simulated irradiation, is reported. This performance is an order of magnitude greater than photomethanation rates achieved over control samples made of nanostructured RuO2 on silicon wafers. The high absorption and unique light‐harvesting properties of the silicon photonic crystal across the entire solar spectral wavelength range coupled with its large surface area are proposed to be responsible for the high methanation rates of the RuO2 photocatalyst. A density functional theory study on the reaction of CO2 with H2 revealed that H2 splits on the surface of the RuO2 to form hydroxyl groups that participate in the overall photomethanation process. Abstract : A nanocrystalline RuO2 supported 3D silicon photonic crystal is shown to be a highly active photomethanation catalyst. The catalyst produces CH4 at a remarkable rate of 4.4 mmol gcat −1 h −1 at ambient temperatures. This exceptional photomethanation rate is due to the large surface area coupled with the unique light‐harvesting properties of the photonic crystal support.